A general, highly enantioselective Michael addition of nitroalkanes to α, β-unsaturated enones catalyzed by 9-amino(9-deoxy)-epi-quinine: a remarkable additive effect. Issue 33 (18th August 2016) - Liu, Siyang; Wang, Qingqing; Ye, Ling; Shi, Zhichuan; Zhao, Zhigang; Yang, Xuejun; Ding, Keyi; Li, Xuefeng
Abstract: A particularly general protocol for the organocatalytic asymmetric Michael addition of nitroalkanes to α, β-unsaturated enones is reported. The Michael reaction proceeded smoothly and provided the desired adducts in moderate to excellent yields (55–99%) and good to excellent enantioselectivities (65–99% ee). The addition of readily available achiral base significantly enhanced the reactivity without compromising the enantioselectivity. Graphical abstract: